EVALUASI FORMULA GEL KOMBINASI BUAH LIDAH BUAYA (Aloe Vera Burm.f) DAN BUAH LABU KUNING (Cucurbita moschata Durch) SEBAGAI PELEMBAP KULIT [EVALUATION OF GEL FORMULA COMBINATIONS OF ALOE VERA (Aloe Vera Burm.f) AND YELLOW PUMPKIN (Cucurbita moschata Durch) AS A SKIN MOISTURIZER] - Sherly Angelina Santoso; Nurista Dida Ayuningtyas (Universitas Pelita Harapan, 2024)
Skin moisturizers are popular in the form of gel products. Natural ingredients that can be used to moisturize the skin are aloe vera and pumpkin, because they contain Î²-carotene which has strong antioxidant activity and flavonoids that can bond the water content in the stratum cSrneum. The combination of HPMC and carbopol 940 in the formulation of gel preparations is used as a gelling agent. The purpose of this study was to determine the effect of variations in the concentration of aloe vera and pumpkin on the physical characteristics of gel preparations and effectiveness in moisturizing the skin. The research steps of the extract were made by maceration method. Moisturizing gel was produced with LB:LK ratio in F1, F2, and F3 respectively (10:10), (12.5:7.5) and (15:5) and F0 as negative without extract. The evaluation included organoleptic test, adhesion, spreadability, pH, viscosity, and testing the effectiveness of the preparation in moisturizing the skin on respondents measured using Skin Moisture Oil Content Analyzer CR-302 Data analysis using one-way ANOVA. The results of the physical evaluation of the gel product organoleptically F0 is transparent, F1-3 is yellow to brownish, semi-solid, and has a distinctive smell of extracts. Analysis of spreadability, adhesion, pH, and viscosity tests showed significant differences between formulas. Formula 3 with LB:LK (15%:5%) ratio produced a moisture value of 51-62% on day 14 which was higher than the other formulas. Bahasa Indonesia Abstract:Pelembab kulit yang digemari oleh masyarakat umumnya dalam bentuk sediaan gel. Bahan alam yang dapat digunakan untuk melembapkan kulit yaitu lidah buaya (LB) dan labu kuning (LK), karena kandungan Î²-karoten yang memiliki aktivitas antioksidan yang kuat dan flavonoid yang dapat mengikat kandungan air pada stratum korneum. Kombinasi HPMC dan karbopol 940 dalam formulasi sediaan gel digunakan sebagai gelling agent. Tujuan penelitian ini untuk mengetahui pengaruh variasi konsentrasi lidah buaya dan labu kuning terhadap karakteristik fisik sediaan gel dan efektivitas dalam melembapkan kulit. Tahapan penelitian ekstrak dibuat dengan metode maserasi. Sediaan gel pelembab dibuat dengan perbandingan LB:LK pada F1,F2, dan F3 secara berturut-turut (10:10), (12,5:7,5) dan (15:5) serta F0 sebagai kontrol negatif tanpa ekstrak. Evaluasi yang dilakukan meliputi uji organoleptis, daya lekat, daya sebar, pH, viskositas, dan pengujian efektivitas sediaan dalam melembapkan kulit pada responden yang diukur menggunakan Skin Moisture Oil Content Analyzer CR-302. Analisis data dilakukan menggunakan one-way ANOVA. Hasil evaluasi fisik sediaan gel secara organoleptis F0 transparan, F1-3 berwarna kuning sampai kecoklatan, berbentuk setengah padat, dan berbau khas ekstrak. Analisis uji daya sebar, daya lekat, pH, dan viskositas menunjukkan adanya perbedaan signifikan antar formula. Formula 3 dengan perbandingan LB:LK (15%:5%) menghasilkan nilai kelembapan 51-62% pada hari ke 14 yang lebih tinggi dibandingkan formula lainnya.